2005
DOI: 10.2174/092986705774370727
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones-A Structural Perspective

Abstract: Xanthones, synthesized or isolated from a natural source, display a wide range of biological and pharmacological activities. In a few cases, their chemical characterization has involved the structure elucidation by single crystal X-ray diffraction. The purpose of this review is to assess in detail this three-dimensional structural data, and thus contribute to a better understanding of the molecular mechanisms involved in the different biological activities presented by xanthones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…In general, it is observed that the three fused rings of the xanthone system adopt a planar conformation [5]. This was also observed for the four compounds studied here analyzing the root mean square (r.m.s.)…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In general, it is observed that the three fused rings of the xanthone system adopt a planar conformation [5]. This was also observed for the four compounds studied here analyzing the root mean square (r.m.s.)…”
Section: Resultssupporting
confidence: 76%
“…Nevertheless, these data just supply information on the bi-dimensional nature of these compounds, and sometimes it can result in an ambiguous determination. Therefore, the single crystal X-ray diffraction (XRD) analysis involving xanthone derivatives are needed to provide very detailed insights into the intraand intermolecular geometry [5]. Although the natural xanthone library is likely to be large, only a small number of structures have been investigated by XRD so far.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, xanthones exhibit diverse biological properties, including antihypertensive, antioxidative, antithrombotic and anticancer activities [37,38]. The xanthone nucleus is known as 9-xanthenone or dibenzo-γ-pyrone [39-41] and its biological activity depends on specific substituents and their positions to the basic structure in the ring system of each molecule [37]. The xanthones used here, III and V, are the most abundant extracted from the heartwood of C. brasiliense .…”
Section: Discussionmentioning
confidence: 99%
“…1 They occur in two major plant families, Guttiferae and Gentianaceae and in some families of fungi and lichens. 2,3 These natural derivatives can present different substitutions in the xanthone core that include hydroxyl, methoxyl, prenyl and glycosyl groups. 4,5 The inclusion of aryl groups has only been reported for a few synthetic derivatives and the 2,3-diaryl moiety has never been presented before our synthetic work.…”
Section: Introductionmentioning
confidence: 99%